Application of Range of Motion (ROM) to Overcome Physical Mobility Disorders in Non-Hemorrhagic Stroke Patients - Syarifudin, Ahmad; Satrio, Trengginas Aji (INDOGENIUS, 2025)
Background & Objective : Ischemic stroke, also known as non-hemorrhagic stroke, is a condition in which blockage of blood vessels leads to partial or complete interruption of blood flow to the brain. This scientific paper aims to analyze nursing care with the intervention of Range of Motion (ROM) exercises in patients with non-hemorrhagic stroke who experience impaired physical mobility. Method : This paper was developed using a case study method. The subject was one patient diagnosed with non-hemorrhagic stroke who had impaired physical mobility at RSD Gunung Jati Cirebon. Data were collected through anamnesis, physical assessment, direct observation, and documentation. The nursing care process was carried out for three days. Result: On admission, the patient complained of pain and difficulty moving the left extremities. The intervention provided was mobilization support through the implementation of Evidence-Based Nursing (EBN) Range of Motion (ROM) exercises. These exercises were implemented for three consecutive days, each session lasting 20 minutes and repeated for each subject. After three days of intervention, evaluation showed improvement in the patient’s physical mobility status, increasing from a score of 3 to 4, indicating that ROM was effective for patients with impaired physical mobility. Conclusion: The application of ROM exercises proved effective in improving physical mobility in patients with non-hemorrhagic stroke. ROM can therefore be recommended as an intervention to support mobilization in stroke patients experiencing impaired mobility.